Fine air pollution particles trapped by street tree barks: In situ magnetic biomonitoring - Chaparro, Marcos Adrián Eduardo (2020)
Particulate air pollution in cities comprises a variety of harmful compounds, including fine iron rich particles, which can persist in the air for long time, increasing the adverse exposure of humans and living things to them. We studied street tree (among other species, Cordyline australis, Fraxinus excelsior and F. pensylvanica) barks as biological collectors of these ubiquitous airborne particles in cities. Properties were determined by the environmental magnetism method, inductively coupled plasma optical emission spectrometry and scanning electron microscopy, and analyzed by geostatistical methods. Trapped particles are characterized as low-coercivity (mean ± s.d. value of remanent coercivity Hcr = 37.0 ± 2.4 mT) magnetite-like minerals produced by a common pollution source identified as traffic derived emissions. Most of these Fe rich particles are inhalable (PM2.5), as determined by the anhysteretic ratio χARM/χ (0.1–1 μm) and scanning electron microscopy (<1 μm), and host a variety of potentially toxic elements (Cr, Mo, Ni, and V). Contents of magnetic particles vary in the study area as observed by magnetic proxies for pollution, such as mass specific magnetic susceptibility χ (18.4–218 × 10−8 m3 kg−1) and in situ magnetic susceptibility κis (0.2–20.2 × 10−5 SI). The last parameter allows us doing in situ magnetic biomonitoring, being convenient because of species preservation, measurement time, and fast data processing for producing prediction maps of magnetic particle pollution. “magnetic biomonitoring using street tree bark is convenient because of measurement time and fast data processing for producing maps of particle air pollution”.